Evaluation of marine pH sensors under controlled and natural conditions for the Wendy Schmidt Ocean Health XPRIZE. (15th May 2017) - Okazaki, Remy R.; Sutton, Adrienne J.; Feely, Richard A.; Dickson, Andrew G.; Alin, Simone R.; Sabine, Christopher L.; Bunje, Paul M. E.; Virmani, Jyotika I.
Abstract: The annual anthropogenic ocean carbon uptake of 2.6 ± 0.5 Gt C is changing ocean composition (e.g., pH) at unprecedented rates, but our ability to track this trend effectively across various ocean ecosystems is limited by the availability of low‐cost, high‐quality autonomous pH sensors. The Wendy Schmidt Ocean Health XPRIZE was a year‐long competition to address this scientific need by awarding $2 million to developers who could improve the performance and reduce the cost of pH sensors. Contestants' sensors were deployed in a series of trials designed to test their accuracy, repeatability, and stability in laboratory, coastal, and open‐ocean settings. This report details the validation efforts behind the competition, which included designing the sensor evaluation trials, providing the conventional true pH values against which sensors were judged, and quantifying measurement uncertainty. Expanded uncertainty (coverage factor k  = 2, corresponding to 95% confidence) of validation measurements throughout the competition was approximately 0.01 pH units. A custom tank was designed for the coastal trials to expose the sensors to natural conditions, including temporal variability and biofouling, in a spatially homogenous environment. The competition prioritized the performance metrics of accuracy, repeatability, and stability over specific applications such as high‐frequency measurements. Although the XPRIZE competition focused on pH sensors, it highlights considerations for testing other marine sensors and measuring seawater carbonate chemistry.